PEMBUATAN DAN KARAKTERISASI ELEKTRODA SELEKTIF ION Pb2+ JENIS KAWAT PERAK TERLAPIS DENGAN IONOFOR 1,10-DIBENZYL-1,10-DIAZA-18-CROWN-6 - Anton Yuntarso; Muji Harsini; Dheasy Herawati; Khoirul Ngibad (Jurnal SainHealth, 2018)
Lead concentration greater than 10 µg/L make health problem among other thing decrease in intelligence, nervous system disorders, so lead rapid analysis with high accuracy and precision is needed. The aim of this research are to know the composition of ESI-Pb2+ membrane silver wire coated type PVC/1,10-dibenzyl-1,10-diaza-18-crown-6, optimum pH condition and to study the characteristic electrode, such as Factor Nernst, range measurement, limit detection, accuracy and precision, selectivity, and blood serum sample accuracy. The result has shown that potensial measurement with Ag/AgCl reference electrode give the best membrane composition of 45 mg PVC, 90 mg NPOE, 10 mg KTCPB, 5 mg 1,10-dibenzyl-1,10-diaza-18-crown-6 in 0,5 ml THF solution. The optimum pH is 3-7 and gave 29,64 mV as Factor Nernst with range measurement 10-1–10-6 M, limit detection was noted at 1,28.10-6 M, and accuracy is 73% - 157% in 10-6–10-1 M Pb2+ solution with variation coefficient 0,70–1,2. The selectivity constanta is K_(i,j)^Pot < 1 toward K+, Ca2+, Mg2+, Na+, Cu2+ dan Fe3+ as interfering ions. Recovery percentage of Ion Selective Electrode Pb2+ silver wire coated type with PVC /1,10-dibenzyl-1,10-diaza-18-crown-6 to blood serum sample has shown 95% - 143% and 110%-117% compare with AAS.